Cadmium from sludge and effluent from Gimboki Sewage Treatment Plant accumulates in the vegetable Telfairia occidentalis - Hlupo, Munyaradzi P (Midlands State University, 2020)
Use of sewage sludge and effluent in cultivation of crops and vegetables is a common practice in Zimbabwe. However, high concentrations of heavy metals such as Cadmium (Cd) in sewage sludge and effluent does not only result in environmental contamination, but may lead to elevated heavy metal uptake by crops, which may affect food quality and safety. The current study aimed to investigate if high concentration of Cd in sludge and effluent from Gimboki Sewage Treatment Plant translates into high concentration of Cd in the leaves of the vegetable Telfairia occidentalis. A total of 20 vegetable samples were analysed for presence of Cd using an Atomic Absorption Spectrophotometer (AAS). Telfairia occidentalis leaves grown under a combination of sludge and effluent had the highest Cd concentration of 24 ± mg kg-1, which was 100 times higher than the EEC (European Economic Commission Regulation) permissible limit of 0.2 mg kg-1. This was followed by leaves of plants grown under effluent only with 6.92 ± mg kg-1, which also exceeded EEC permissible limit by 35 times. Remarkably, T. occidentalis leaves of plants grown with neither sludge nor effluent did not have any detectable Cd concentration. It can be concluded that high concentrations of Cd in sewage effluent and sludge led to accumulation of Cd in pumpkin leaves thereby compromising the quality and safety of the vegetables for human consumption. I therefore recommend that farmers at Gimboki Sewage Treatment Plant should desist from using sludge and effluent for manuring and watering their crops.